2010
DOI: 10.1186/1475-2875-9-18
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent screening and treatment versus intermittent preventive treatment of malaria in pregnancy: user acceptability

Abstract: BackgroundMalaria in pregnancy is associated with increased risks of maternal and foetal complications. Currently, intermittent preventive treatment (IPT) of malaria during pregnancy with sulphadoxine-pyrimethamine (SP) is recommended by the WHO as part of a package of interventions also including insecticide-treated nets and effective case management. However, with increasing resistance to SP, the effectiveness of SP-IPT has been questioned. A randomized controlled trial (RCT) to investigate the relative effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 25 publications
7
63
0
Order By: Relevance
“…Many pregnant women agreed with the idea of being tested for an infection before receiving treatment citing the discomfort of side effects of unnecessary drugs. This is in line with findings of other studies exploring the acceptability of ISTp in Ghana and Kenya [27, 28, 30]. The importance of clear communication in relation to what the tests are for, and their results was emphasized by both pregnant women and health workers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Many pregnant women agreed with the idea of being tested for an infection before receiving treatment citing the discomfort of side effects of unnecessary drugs. This is in line with findings of other studies exploring the acceptability of ISTp in Ghana and Kenya [27, 28, 30]. The importance of clear communication in relation to what the tests are for, and their results was emphasized by both pregnant women and health workers.…”
Section: Discussionsupporting
confidence: 89%
“…As seen elsewhere [27–30], this study found that pregnant women do not attend ANC solely for malaria screening; they want the progress of their babies’ development to be monitored to increase the chance that the baby will be born healthy and without complications. Furthermore, the study findings strongly suggest that the likelihood of pregnant women complying with repeat visits is related to the quality of services and care that they received.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, it appears that most women can be persuaded to accept medication if the benefits are pointed out by a qualified health care provider. This confirms that women’s trust in health workers’ judgement plays a crucial role in ensuring high IPTp uptake, which has been highlighted by a number of previous studies [28–30]. …”
Section: Resultssupporting
confidence: 83%
“…The initial refusals and withdrawals in Mali, though small in number, were concentrated in an area of greater socio-economic diversity with more educated residents, and seemed to reflect a degree of scepticism regarding the trial, which could also affect willingness to try a new intervention. This motivation to comply with sanctioned health activities also emerged in the studies of IPTi [20] and in the comparison of IPTp with IST [27]. A growing literature around the ethics of trial participation has explored the important role of social relations in trials [22], [28], [29] and found that “interactions and relationships between researchers and community members, and within the community, play a critical role in participants' perceptions of a study” [28].…”
Section: Discussionmentioning
confidence: 99%